2019
DOI: 10.1091/mbc.e19-01-0074
|View full text |Cite
|
Sign up to set email alerts
|

Central-spindle microtubules are strongly coupled to chromosomes during both anaphase A and anaphase B

Abstract: Spindle microtubules, whose dynamics vary over time and at different locations, cooperatively drive chromosome segregation. Measurements of microtubule dynamics and spindle ultrastructure can provide insight into the behaviors of microtubules, helping elucidate the mechanism of chromosome segregation. Much work has focused on the dynamics and organization of kinetochore microtubules, that is, on the region between chromosomes and poles. In comparison, microtubules in the central-spindle region, between segrega… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 63 publications
12
60
0
Order By: Relevance
“…We found bridging fibers to be essential for the separation of displaced kinetochores, and continuous cutting of most interpolar MTs in the central spindle also decreased spindle elongation rates (Vukušićet al, 2017). In agreement with the latter result, a single-hit laser ablation of all interpolar MTs in human cells immediately stopped anaphase chromosome motion for a short period of time (Yu et al, 2019). This is reminiscent of the pioneering ablation experiments showing that chromosomes continue to move poleward after centrosome removal as long as the k-fiber stub is longer than 1 µm (Nicklas, 1989;Nicklas et al, 1982), as previously mentioned.…”
Section: Powering Versus Braking Chromosome Segregationsupporting
confidence: 85%
See 3 more Smart Citations
“…We found bridging fibers to be essential for the separation of displaced kinetochores, and continuous cutting of most interpolar MTs in the central spindle also decreased spindle elongation rates (Vukušićet al, 2017). In agreement with the latter result, a single-hit laser ablation of all interpolar MTs in human cells immediately stopped anaphase chromosome motion for a short period of time (Yu et al, 2019). This is reminiscent of the pioneering ablation experiments showing that chromosomes continue to move poleward after centrosome removal as long as the k-fiber stub is longer than 1 µm (Nicklas, 1989;Nicklas et al, 1982), as previously mentioned.…”
Section: Powering Versus Braking Chromosome Segregationsupporting
confidence: 85%
“…By using a laser ablation assay (Buđa et al, 2017), we observed that these bridging fibers moved together with sister kinetochores and their k-fibers, indicating strong crosslinking between these structures during metaphase (Kajtez et al, 2016;Milas and Tolic, 2016;Tolic, 2018; and anaphase (Vukušićet al, 2017). In agreement with the observation of bridging MTs in anaphase (Vukušićet al, 2017), recent large-scale electron tomography reconstructions of spindles in human cells reported different classes of interpolar MTs that were often tightly associated into bundles contacting k-fibers (Yu et al, 2019). It will be interesting to identify the crosslinkers that keep k-fibers and bridging fibers laterally linked, with the kinesins Eg5 (also known as Kif11) and Kif15 being good candidates as they are involved in the regulation of neighboring k-fiber coupling during metaphase (Vladimirou et al, 2013).…”
Section: Coupling Of Depolymerizing Mts To Spindle Poles and Kinetochsupporting
confidence: 74%
See 2 more Smart Citations
“…4E). Sliding forces generated in the midzone antiparallel region by these modules are then transmitted to spindle poles most probably through their lateral connections to k-fibers (4,31). Finally, it would be interesting to study the details of signalling cascade that regulates spindle elongation in human cells where Aurora kinases are promising candidates that could separately regulate both sliding modules (30,32,33).…”
mentioning
confidence: 99%